Searching, Navigating, and Recommending Movies through Emotions: A Scoping Review - Nuno Piçarra; Eduardo Reis; Teresa Chambel; Patrícia Arriaga (Human Behavior and Emerging Technologies)
Movies offer viewers a broad range of emotional experiences, providing entertainment, and meaning. Following the PRISMA-ScR guidelines, we reviewed the literature on digital systems designed to help users search and browse movie libraries and offer recommendations based on emotional content. Our search yielded 83 eligible documents (published between 2000 and 2021). We identified 22 case studies, 34 empirical studies, 26 proof of concept, and one theoretical paper. User transactions (e.g., ratings, tags) were the preferred source of information. The documents examined approached emotions from both a categorical (n=35) and dimensional (n=18) perspectives, and nine documents offer a combination of both approaches. Although there are several authors mentioned, the references used are frequently dated, and 12 documents do not mention author or model used. We identified 61 words related to emotion or affect. Documents presented on average 1.36 positive terms and 2.64 negative terms. Sentiment analysis (n=31) is frequently used for emotion identification, followed by subjective evaluations (n=15), movie low-level audio and visual features (n = 11), and face recognition technologies (n=8). We discuss limitations and offer a brief review of current emotion models and research.